PENGARUH PROFITABILITAS, LIKUIDITAS, AKTIVITAS, STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BEI PERIODE 2018-2022) - Gusti Ayu, Ratih Hapsari (Jurnal Riset Akuntansi, 2024)
The purpose of this study is to analyze the impact of the profitability, liquidity, activity, capital structure and dividend policy ratio projected by ROE, CR, TATO, LTDER and the DPR on the Value of the PBV Proxy Company in part on the energy sector companies listed on the Indonesian Stock Exchange 2018-2022. Quantitative associative is this type of research, whereas the data collected using the sample survey method is a documentation study technique. Of the 80 companies, there are 13 samples of companies that meet the purposive sampling criteria. Using the double linear regression method with the help of the SPSS application. The results of research using the T-Test showed that profitability had a positive and significant impact on the Company's Value. Liquidity and Capital Structure had a negative and significant effect on the company's Values. While the Ratio of Activity and Dividend Policy had positive and non-significant effects on the value of the Company.